2022
DOI: 10.3390/s22103892
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of the Effect of Mechanotactile Feedback Location on Myoelectric Prosthesis Performance Using a Sensorized Prosthetic Hand

Abstract: A commonly cited reason for the high abandonment rate of myoelectric prostheses is a lack of grip force sensory feedback. Researchers have attempted to restore grip force sensory feedback by stimulating the residual limb’s skin surface in response to the prosthetic hand’s measured grip force. Recent work has focused on restoring natural feedback to the missing digits directly through invasive surgical procedures. However, the functional benefit of utilizing somatotopically matching feedback has not been evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…The MAPP's previously-published design [67] was altered to improve wearer comfort in our study-the distal ring was made to resemble the oval shape of a wrist and the hand brace was elongated so that the distal ring would sit more proximally on the wearer's wrist. A 3D-printed robotic hand [68] participant's hand. Wrist rotation capabilities were also added to the device.…”
Section: Simulated Prosthesis and Donning Proceduresmentioning
confidence: 99%
“…The MAPP's previously-published design [67] was altered to improve wearer comfort in our study-the distal ring was made to resemble the oval shape of a wrist and the hand brace was elongated so that the distal ring would sit more proximally on the wearer's wrist. A 3D-printed robotic hand [68] participant's hand. Wrist rotation capabilities were also added to the device.…”
Section: Simulated Prosthesis and Donning Proceduresmentioning
confidence: 99%
“…Although, the remaining three participants did not comment on that notion. Wells et al ( 2022 ) reported similar findings, where the mechanotactile feedback resulted in an increased time to finish a task. The respective authors believe this effect to be due to the added focus on the task with feedback.…”
Section: Discussionmentioning
confidence: 72%
“…The MAPP’s previously-published design [30] was altered to improve wearer comfort in our study—the distal ring was made to resemble the oval shape of a wrist and the hand brace was elongated so that the distal ring would sit more proximally on the wearer’s wrist. A non-proprietary 3D-printed robotic hand [31] was affixed to the MAPP beneath the participant’s hand. Wrist rotation capabilities were also added to the device.…”
Section: Methodsmentioning
confidence: 99%